Black women and the struggle for equality: for a decolonial black feminism - Raul, Jessica Mara (2016)
This work starts with a reflection on the feminist experience from a decolonial perspective. To do so, it takes into account the asymmetries in the Brazilian women’s movement and highlights the organizational strategies of the black women’s movement, which considers the situation of women in the diaspora in the southern hemisphere through their experiences. It intends to demonstrate how the differences established by instruments that rank human beings kept the black population at the base of the social pyramid, with even greater losses for black women who are subject to the intersectionality of race, gender and class oppression as barriers to active citizenship. Thus, the everyday experiences of these women, combined with their struggle for survival, provides these women not only with a means of resistance to the standard established by the hierarchical logic in the acquisition of social goods, but also with a privileged viewing point for the analysis of this society.